Synthesis and characterization of highly luminescent CuInS(2) and CuInS(2)/ZnS (core/shell) nanocrystals - Kuo, Kuan-Ting; Chen, San-Yuan; Cheng, Bing-Ming; Lin, Chin-Ching (My University, 2008)
High-quality CuInS(2)/ZnS (core-shell) nanocrystals (NCs) were synthesized via a colloidal solvent process and characterized for their optical properties by UV-vis, room temperature solution photoluminescence (PL) spectroscopy, and further obtained powders were characterized by X-ray microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and dynamic light scattering (DLS). diffraction (XRD), transmission electron The obtained CIS and CIS/ZnS core/shell NCs are quasimonodisperse with an average particle size of 2.4 and 4.6 nm, respectively. All of the as-synthesized NCs can be well dispersed in toluene or hexane to form stable and clear colloidal solutions, which show strong visible emission (blue for CIS/ZnS core/shell NCs) under UV excitation. The growth of a ZnS shell on CIS NCs, that is, the formation of CIS/ZnS core/shell NCs, resulted in an impact enhancement in the PL intensity compared to that of bare CIS NCs due to the eliminated surface defects and the reduced lattice mismatch between the core and shell materials. A dramatic increase of the PL intensity can be obtained from the ZnS-capped CIS with respect to that of the bare CIS NCs. (C) 2008 Elsevier B.V. All rights reserved.